YES Problem: f(g(x)) -> g(f(f(x))) f(h(x)) -> h(g(x)) f'(s(x),y,y) -> f'(y,x,s(x)) Proof: DP Processor: DPs: f#(g(x)) -> f#(x) f#(g(x)) -> f#(f(x)) f'#(s(x),y,y) -> f'#(y,x,s(x)) TRS: f(g(x)) -> g(f(f(x))) f(h(x)) -> h(g(x)) f'(s(x),y,y) -> f'(y,x,s(x)) Usable Rule Processor: DPs: f#(g(x)) -> f#(x) f#(g(x)) -> f#(f(x)) f'#(s(x),y,y) -> f'#(y,x,s(x)) TRS: f(g(x)) -> g(f(f(x))) f(h(x)) -> h(g(x)) Matrix Interpretation Processor: dim=1 usable rules: f(g(x)) -> g(f(f(x))) f(h(x)) -> h(g(x)) interpretation: [f'#](x0, x1, x2) = 2x0 + 5/2x1 + 1, [f#](x0) = 1/2x0, [s](x0) = 2x0 + 2, [h](x0) = 3, [f](x0) = x0, [g](x0) = 2x0 + 3 orientation: f#(g(x)) = x + 3/2 >= 1/2x = f#(x) f#(g(x)) = x + 3/2 >= 1/2x = f#(f(x)) f'#(s(x),y,y) = 4x + 5/2y + 5 >= 5/2x + 2y + 1 = f'#(y,x,s(x)) f(g(x)) = 2x + 3 >= 2x + 3 = g(f(f(x))) f(h(x)) = 3 >= 3 = h(g(x)) problem: DPs: TRS: f(g(x)) -> g(f(f(x))) f(h(x)) -> h(g(x)) Qed